Want to operate an abdominal lump? Think twice; it might be spontaneous rectus sheath hematoma: a case report - Sarkar, Manisha; Mitra, Sukla (International Journal of Research in Medical Sciences, 2016)
Rectus sheath hematoma is a rare, but potentially misdiagnosed clinical entity. It occurs when there is direct tear in the rectus abdominis muscle fibres or in the supplying blood vessels. It may be associated with trauma, raised intra-abdominal pressure, or muscle weakness. When non-traumatic, the condition is termed as spontaneous rectus sheath hematoma. Because of its rarity, spontaneous rectus hematoma can be easily missed, endangering patient management. With progressively increasing use of anticoagulant and antiplatelet agents, the incidence of this pathology is rising. We are reporting a case of spontaneous rectus sheath hematoma in a 56 year old female, known diabetic, hypertensive with dyslipidaemia on combination drug therapy but not on anticoagulant/antiplatelet medications, that was clinically misdiagnosed as omental hernia. The main presenting complaint was swelling in abdomen for 1 month. There was no history of trauma. Radiologic findings showed hypoechoic multiloculated complex cystic lesion. Cytological findings showed features of old hematoma. This case report intends to increase awareness in considering rectus sheath hematoma as an important differential diagnosis of lump abdomen. Rectus sheath hematoma, a rarely seen pathology, often confuses clinicians leading to unnecessary negative laparotomies. Definitive operative procedure should not be undertaken depending on sonographic findings alone, as the images are prone to subjective error. The main treatment modality of rectus sheath hematoma is conservative management.